Autoantibody-Specific Signalling in Pemphigus - Schmitt, Thomas; Waschke, Jens (Frontiers in Medicine, 2021)
Pemphigus is a severe autoimmune disease impairing barrier functions of epidermis and mucosa. Autoantibodies primarily target the desmosomal adhesion molecules desmoglein (Dsg) 1 and Dsg 3 and induce loss of desmosomal adhesion. Strikingly, autoantibody profiles in pemphigus correlate with clinical phenotypes. Mucosal-dominant pemphigus vulgaris (PV) is characterized by autoantibodies (PV-IgG) against Dsg3 whereas epidermal blistering in PV and pemphigus foliaceus (PF) is associated with autoantibodies against Dsg1. Therapy in pemphigus is evolving towards specific suppression of autoantibody formation and autoantibody depletion. Nevertheless, during the acute phase and relapses of the disease additional treatment options to stabilize desmosomes and thereby rescue keratinocyte adhesion would be beneficial. Therefore, the mechanisms by which autoantibodies interfere with adhesion of desmosomes need to be characterized in detail. Besides direct inhibition of Dsg adhesion, autoantibodies engage signalling pathways interfering with different steps of desmosome turn-over. With this respect, recent data indicate that autoantibodies induce separate signalling responses in keratinocytes via specific signalling complexes organized by Dsg1 and Dsg3 which transfer the signal of autoantibody binding into the cell. This hypothesis may also explain the different clinical pemphigus phenotypes.